IMAGING DIAGNOSIS—RADIOGRAPHY AND COMPUTED TOMOGRAPHY OF RADIOULNAR ISCHEMIC NECROSIS IN A JACK RUSSELL TERRIER. Issue 1 (2nd November 2016) - Schmid, Lisbeth; Klang, Andrea; Katic, Nikola; Ansón, Agustina; Gumpenberger, Michaela; Kneissl, Sibylle
Abstract: A 7‐year‐old Jack Russell Terrier with a history of minor trauma was presented for lameness of the left forelimb. Radiography and computed tomography demonstrated a localized radioulnar osteolytic lesion with cortical bone loss and enthesiophytes. Based on results of diagnostic imaging and histopathological examination, the final diagnosis was radioulnar ischemic necrosis (RUIN), complicated by pathologic fracture. A rare disorder of unknown etiology, RUIN may be secondary to tearing of the interosseous ligament and potential ischemia. It should be differentiated from neoplastic or fungal disease. To the authors´ knowledge, this is the first canine case report describing RUIN.